A 10-Year Study on Larynx Preservation Compared With Surgical Resection in Patients With Locally Advanced Laryngeal and Hypopharyngeal Cancers - Su, Xuan; He, Hui-Chan; Ye, Zu-Lu; Zhou, Da-Lei; Liu, Qing; Yang, Xin-Hua; Long, Ya-Kang; Tang, Tao; Ma, Jiang-Jun; Xu, Bo-Heng; Chen, Wei-Chao; He, Cai-Yun; et al. (Frontiers in Oncology, 2020)
Background Few reports from China provide confirmed evidence of the effectiveness of the larynx preservation strategy compared with surgery on the treatment of laryngeal and hypopharyngeal cancers. This study assessed the clinical outcomes of patients with locally advanced laryngeal and hypopharyngeal cancers treated with larynx preservation and determined the optimal larynx preservation procedure. Methods Data of 1,494 patients treated with total laryngectomy or larynx preservation between 2006 and 2014 were retrieved from the database of Sun-Yat Sen University Cancer Center in Guangzhou, China, and 366 eligible patients were selected for final analysis. The clinical outcomes of 228 patients received total laryngectomy and 138 patients received larynx preservation treatments, which comprises induction followed by radiotherapy and concurrent radio-chemotherapy, were compared. Results There was no statistical difference in the 3-, 5-, and 10-year PFS and OS in patients received larynx preservation compared with patients treated with laryngectomy. With respect to T stage, a better overall OS in T2-stage disease (P = 0.036) but poorer PFS (P = 0.005) in T3-stage disease was observed in the larynx preservation group compared with the surgery group in Univariate analysis. T3-stage disease had poorer PFS in multivariable analysis (P = 0.022). With larynx preservation intent, induction chemotherapy followed by radiotherapy showed no advantage in the control of disease progression and survival compared with concurrent chemoradiotherapy. The patient subpopulations who received efficacy assessment after induction chemotherapy exhibited significantly longer PFS and OS compared with those without efficacy assessment. Conclusions This is the largest sample size study on larynx preservation treatment for laryngeal and hypopharyngeal cancers in China. Our results indicated that larynx preservation treatments did not jeopardize the survival of patients with advanced resectable laryngeal or hypopharyngeal cancers. Efficacy assessment should be emphasized in induction chemotherapy.